Pengaruh Karakteristik Khusus Auditor Signature dan Karakteristik Perusahaan terhadap Audit Delay - Antohni, Annisa Rosyida; Triani, Ni Nyoman Alit (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Delay in the publication of financial statements affects the credibility of the company. POJK regulation number 14 of 2022 regulates the provisions of sanctions for companies that are not on time. The maximum deadline for submitting financial statement audit results is the end date of the third month after the fiscal year. This study analyzes the effect of auditor signature special characteristics and company characteristics with sample of 427 companies listed on the IDX for the 2021 period. The approach used in quantitative with multiple linear regression analysis methods. The results showed that the company size and profitability variables had an effect on audit delay. However, the variables of gender, education level, company age, and leverage have no effect on audit delay.